Tübingen hip flexion splint more successful than Pavlik harness for decentred hips after the age of three months. (1st May 2021) - Lyu, XueMin; Chen, Tao; Yang, Zheng; Fu, Gang; Feng, Chao; Zhang, Tao; Lu, Ming
Abstract : Aims: The objective of this study was to evaluate the clinical and radiological outcomes of patients younger than six months of age with developmental dysplasia of the hip (DDH) managed by either a Pavlik harness or Tübingen hip flexion splint. Methods: Records of 251 consecutive infants with a mean age of 89 days (SD 47), diagnosed with DDH between January 2015 and December 2018, were retrospectively reviewed. Inclusion criteria for patients with DDH were: younger than 180 days at the time of diagnosis; ultrasound Graf classification of IIc or greater; treatment by Pavlik harness or Tübingen splint; and no prior treatment history. All patients underwent hip ultrasound every seven days during the first three weeks of treatment and subsequently every three to four weeks until completion of treatment. If no signs of improvement were found after three weeks, the Pavlik harness or Tübingen splint was discontinued. Statistical analysis was performed. Results: The study included 251 patients with Graf grades IIc to IV in 18 males and 233 females with DDH. Mean follow-up time was 22 months (SD 10). A total of 116 hips were graded as Graf IIc (39.1%), nine as grade D (3.0%), 100 as grade III (33.7%), and 72 as grade IV (24.2%). There were 109 patients (128 hips) in the Pavlik group and 142 patients (169 hips) in the Tübingen group (p = 0.227). The Tübingen group showed a 69.8% success rate in Graf III and Graf IV hips while the success rate was significantly lower in the Pavlik group, 53.9% (p = 0.033). For infants older than three months of age, the Tübingen group showed a 71.4% success rate, and the Pavlik group a 54.4% success rate (p = 0.047). Conclusion: The Tübingen splint should be the preferred treatment option for children older than three months, and for those with severe forms of DDH such as Graf grade III and IV, who are younger than six months at time of diagnosis. The Tübingen hip flexion splint is a valid alternative to the Pavlik harness for older infants and those with more severe DDH. Cite this article: Bone Joint J  2021;103-B(5):991–998.